Analysis of Resist Printing Using Pigment Dyes - Haris, Muhammad Naoval; Sasongko, Aditya Dimas Wahyu; Murty, Daru Anggara; Widadi, Zahir; Agama, Dimas Pandu Setia (P3M Politeknik Negeri Media Kreatif, 2024)
Resist printing is one of the textile printing techniques that utilizes the difference in affinity between dyes and resist agents to create patterns or motifs on fabric. This study aims to evaluate the efficiency of this method in producing patterns with good color fastness and optimal motif sharpness. The resist agent used is Diammonium Phosphate (DAP). Pigment dyes were chosen due to their water-insoluble characteristics, requiring an emulsion thickener to adhere to the fabric fibers. The study involves the use of varying concentrations of reactive dyes during the dyeing process and variations in the timing of alkali addition during and after the fixation process. The results of the color fastness test to washing and rubbing showed generally good outcomes and can be further improved to enhance motif clarity in the future.